Design of helical-blade rotor of Vertical Axis Wind Turbine (VAWT) - Junaidin, Buyung (Institut Teknologi Dirgantara Adisutjipto, 2020)
The vertical axis wind turbine (VAWT) with helical-blade has been developed, manufactured and applied in almost all developed countries. In Indonesia, vertical axis wind turbines are still not widely applied compared to horizontal axis wind turbines. Vertical axis wind turbines with helical-blade are still very rare in Indonesia. Research and development of the vertical axis wind turbine are needed because of its advantages compared to horizontal axis wind turbine. The advantages are: can operate in various wind directions, lower noise due to smaller tip speed ratio (TSR) and for large-scale, mechanical and electrical systems of turbine can be placed on ground. The aim of this research is to design a vertical axis wind turbine rotor with helical-blade that can be applied at low speeds and changing direction wind condition, such as urban wind characteristics. Performance analysis of wind turbine rotor is done by using double-multiple stream-tube (DMS) model approach. This research yields a rotor of vertical axis wind turbine with helical-blade with rotor length and diameter are 2m and 1m respectively, the rotor blade airfoil is DU-06-W-200 with chord length is 0.2m. From analysis, the optimum tip speed ratio of the rotor is 2.6 with a maximum power coefficient is 0.57.